Role of nutrition in curing dysphagia: a case series of five rare cases of severe acute malnutrition with severe megaloblastic anaemia - Parikh, Rujuta; Mudaliar, Sangeeta; Prabhu, Sanjay; Bodhanwala, Minnie (International Journal of Contemporary Pediatrics, 2023)
Severe acute malnutrition (SAM) is associated with multiple vitamin deficiencies, including vitamin B12. Vitamin B12 deficiency is commonly found in the Indian subcontinent, and has devastating clinical consequences. It leads to megaloblastic anaemia and several other complications. Dysphagia is an unusual symptom of the same. The present study was undertaken to evaluate the reversal of dysphagia with vitamin B12 supplements. A hospital-based retrospective case series was conducted at the B. J. Wadia Hospital for Children. Cases were collected from 19 November 2021, to 25 August 2022. Five children less than two years of age, who presented with complaint of dysphagia, presence of megaloblastic anaemia and concurrent nutritional compromise were evaluated for their clinical profiles, and the outcomes were analysed. We found that dysphagia was a reversible symptom with medical nutrition therapy and injectable B12 therapy in children with SAM who had severe megaloblastic anaemia. The present study has identified the prevalence of dysphagia in cases of SAM with megaloblastic anaemia. This dysphagia is reversible and curable with nutritional rehabilitation and injectable B12 therapy without any further invasive intervention.